Experimental study on seismic performance of RC frames with Energy-Dissipative Rocking Column system. (1st September 2019) - Li, Yan-Wen; Li, Guo-Qiang; Jiang, Jian; Wang, Yan-Bo
Highlights: A novel system of steel Energy-Dissipative Rocking Column (EDRC) is proposed to mitigate seismic responses of reinforced concrete Moment Resisting Frames (MRFs). Pseudo-dynamic tests are conducted on two-storey two-bay reinforced concrete frames, with and without EDRC, respectively. Post-earthquake behavior of these two systems is also compared through quasi-static cyclic tests. The experimental results show that the presence of EDRC can effectively mitigate the maximum, residual and inhomogeneous of inter-storey drifts, and thus prevent the soft storey failure of MRFs. Abstract: The conventional reinforced concrete Moment Resisting Frames (MRFs) have suffered from soft story failure during major earthquake events. A novel system of steel Energy-Dissipative Rocking Column (EDRC) is proposed to mitigate seismic responses of MRFs. Pseudo-dynamic tests are conducted on large-scale two-story and two-bay reinforced concrete frames, with and without EDRC, respectively. The post-earthquake behavior of these two systems is also compared through quasi-static cyclic tests. The experimental results show that the presence of EDRC can effectively mitigate the maximum value, residual value and inhomogeneous distribution of inter-story drifts, and thus prevent the soft story failure of MRFs. It is found that the maximum and residual inter-story drift of combined MRF and EDRC systems is reduced by 26.0% and 82.0%, respectively, compared to pure MRFs. The inhomogeneous degree of inter-story drifts can be reduced by 25.0% and 11.0%, respectively, in the pseudo-dynamic and quasi-static tests.